Fighting Corruption in Public Services : Chronicling Georgia's Reforms - World Bank (World Bank, 2012)
This book chronicles the anticorruption reforms that have transformed public service in Georgia since the Rose Revolution in late 2003. The focus is on the 'how' behind successful reforms of selected public services. This book tries to answer some of these questions. It is based largely on data and informed by interviews with past and current high-ranking government officials who provide insights from within government on the challenges and solutions, the decisions, and the trade-offs considered. This book does not assess Georgia's overall reforms since the rose revolution. It does not address efforts toward democratization, which were a key part of the rose revolution. The book focuses on how the state was able to root out corruption and eliminate red tape in selected public services. It does not analyze areas in which government efforts are still continuing or may have fallen short. Nor does it suggest any causality between anticorruption reforms and growth or social outcomes. From the case studies on each of these efforts, the book identifies a set of common factors that led to the success of the reforms.